2020
DOI: 10.37285/ijpsn.2020.13.4.7
|View full text |Cite
|
Sign up to set email alerts
|

A New RoVe Method to Purify Endophytic Fungi from Medicinal Plants Western Ghats of Karnataka India

Abstract: Endophytic fungi from medicinal plants were hardly ever reported as compared to those from soil and marine sources. The present results associate the presence of endophytic fungi in medicinal plants by isolating them from three medicinal plants i.e. Bombax ceiba, Aloe vera, and Ximenia americana. In the present research investigation, surface sterilization method and media were standardized, and 32 endophytic fungi were isolated from three medicinal plants. We assessed the competence of three different surface… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Moreover, thermozymes can be utilized as models for comprehension thermo soundness. Consequently, distinguishing underlying highlights associated with strength of thermozymes is fundamental for a hypothetical portrayal of the physico-compound standards adding to protein strength and collapsing [11,22]. Besides, this data is fundamental likewise for planning more steady proteins for modern cycles.…”
Section: Thermoenzymesmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, thermozymes can be utilized as models for comprehension thermo soundness. Consequently, distinguishing underlying highlights associated with strength of thermozymes is fundamental for a hypothetical portrayal of the physico-compound standards adding to protein strength and collapsing [11,22]. Besides, this data is fundamental likewise for planning more steady proteins for modern cycles.…”
Section: Thermoenzymesmentioning
confidence: 99%
“…Totalled prion atoms are firmly impervious to traditional proteases and various techniques utilized for microbe inactivation, including autoclaving at 121 °C. Ongoing examinations have shown that amyloid type of prion can be corrupted by some microbial proteases using denaturing pre-treatments, like pre-warming and treatment with cleansers [21,22,28]. Promising wellspring of chemicals corrupting PrPSc without cleansers or under non-basic conditions are some thermophiles and microorganisms having a place with the family of Streptomyces [7,9,12,23,27,28].…”
Section: Applications Of Thermoenzymesmentioning
confidence: 99%